Numerical analysis of heat and mass transfer of a moving porous moist object in a two dimensional channel - Selimefendigil, Fatih; Coban, Seda Ozcan; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2021)
The aim of this study is to investigate heat and mass transfer during convective drying of a moving porous medium in a 2D rectangular channel with laminar flow conditions. Finite element method is used with ALE to model the movement of the porous moist object. Hot dry air with different temperatures flowed in the channel with varying velocities and the porous object also has a movement with parallel direction to the flow. The code is validated by using experimental results. Results indicated that the heat transfer coefficient of the moving porous moist object is time dependent and varying locally. Significant impacts of increasing values of air temperature and velocity on the heat and mass transfer features are observed.
Keywords: Heat and mass transfer; Moving porous object; Convective drying; CFD